Falls. Issue 2 (18th March 2013) - Frith, James; Davison, John
Summary: Falls and fall-related injury are common and become more prevalent with increasing age. Risk factors for falling are numerous, synergistic and complex, and require multidisciplinary assessment. The evidence base for intervention strategies continues to improve, but is often limited by the methodological difficulties that are inherent in falls research. The most effective intervention is a multifactorial approach that targets identified risk factors. Multicomponent exercise, either in a group or individually, is one of the most effective components of intervention. Other successful components include home hazard modification and psychotropic medication withdrawal. Primary prevention does not appear to be cost effective, but secondary prevention far outweighs the cost of falls and fall-related injury.